Metastasis-Induced Acute Pancreatitis Successfully Treated with Chemotherapy and Radiotherapy in a Patient with Small Cell Lung Cancer - Kerem Okutur; Mustafa Bozkurt; Taner Korkmaz; Ercan Karaaslan; Levent Guner; Suha Goksel; Gokhan Demir (Case Reports in Oncological Medicine)
Although involvement of pancreas is a common finding in small cell lung cancer (SCLC), metastasis-induced acute pancreatitis (MIAP) is very rare. A 50-year-old female with SCLC who had limited disease and achieved full response after treatment presented with acute pancreatitis during her follow-up. The radiologic studies revealed a small area causing obliteration of the pancreatic duct without mass in the pancreatic neck, and endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) confirmed the metastasis of SCLC. The patient was treated successfully with systemic chemotherapy and radiotherapy delivered to pancreatic field. In SCLC, cases of MIAP can be encountered with conventional computed tomography with no mass image, and positron emission tomography and EUS-FNA can be useful for diagnosis of such cases. Aggressive systemic and local treatment can prolong survival, especially in patients with good performance status.